Neuropeptide S modulates the amygdaloidal HCN activities (Ih) in rats: Implication in chronic pain. (June 2016) - Zhang, Shuzhuo; You, Zerong; Wang, Shuxing; Yang, Jinsheng; Yang, Lujia; Sun, Yan; Mi, Wenli; Yang, Liling; McCabe, Michael F.; Shen, Shiqian; Chen, Lucy; Mao, Jianren
Abstract: Neuropeptide S (NPS), an endogenous anxiolytic, has been shown to protect against chronic pain through interacting with its cognate NPS receptor (NPSR) in the brain. However, the cellular mechanism of this NPS action remains unclear. We report that NPS inhibits hyperpolarization-activated cyclic nucleotide-gated (HCN) channel current ( Ih ) in the rat's amygdala through activation of NPSR. This NPS effect is mediated through ERK1/2 phosphorylation in a subset of pyramidal-like neurons located in the medial amygdala. The characters of the recorded Ih suggest a major role for HCN1 activity in this process. Inhibition of Ih by NPS stimulates the glutamatergic drive onto fast spiking intra-amygdalolidal GABAergic interneurons, which in turn facilitates GABA release onto pyramidal-like neurons. Moreover, the HCN1 expression is increased in the amygdala of rats with peripheral nerve injury and intra-amygdaloidal administration of the HCN channel inhibitor ZD7288 attenuates nociceptive behavior in these rats. These results suggest that NPS-mediated modulation of intra-amygdaloidal HCN channel activities may be an important central inhibitory mechanism for regulation of chronic pain. Highlights: NPS inhibits HCN activities ( I h ) in the amygdala. ERK1/2 phosphorylation is a cellular mechanism underlying NPS inhibition of I h . HCN1 subunits contribute to the kinetics of I h in the amygdala. NPS facilitates GABA release through I h inhibition. Inhibition of I h with ZD7288 in the amygdala ameliorates chronic pain.